Regulation of Intellectual Property Rights (IPR) in Artworks by Robots and Algorithms - Raevita, Febrina; Uzma, Nur Lailatuka Syafa’atul; Alfarizy, Muhammad (Begawan Abioso, 2024)
The regulation of Intellectual Property Rights (IPR) in works of art by robots and algorithms is a controversial subject due to the ability of Artificial Intelligence (AI) to produce works of art that closely resemble human intelligence independently. In situations of commercial use, legal and ethical problems arise when digital works are created without the permission of the original copyright owner. The aim of this research is to determine the identification of copyright owners in the context of works of art created by robots and algorithms, as well as explain the protection of moral and commercial rights for creators of works of art that involve the use of robotic technology and algorithms. This research uses normative juridical methods and analytical descriptive approaches to analyze documents, regulations, and other reference sources related to the issue under study. The results of this research show that artificial intelligence has the ability to work independently, produce products, and make creative judgments alone. In most cases, programmers consist of individuals who enter data and algorithms. The main task of artificial intelligence is to understand and develop real results based on commands. With this, we can create an environment that supports creativity and innovation while respecting individual rights and encouraging fair and ethical use of digital works.